Внесок Д.Б. Рахметова в інтродукцію рослин і розвиток агросфери України - Moroz, P.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
The paper deals with the results of D.B. Rakhmetov in the enrichment of plant resources and development of agrosphere of Ukraine.